Immunophenotyping Tracks Motor Progression in Parkinson’s Disease Associated with a TH Mutation - Gopinath, Adithya; Ramirez-Zamora, Adolfo; Franks, Stephen; Riaz, Tabish; Smith, Aidan; Dizon, Glen; Hornstein, Lauryn; Follett, Jordan; Swartz, Camille; Bravo, Jonathan; Kugelmann, E. Lee; Farrer, Matthew; et al. (Journal of Parkinson's disease, 2024)
Background: Parkinson’s disease (PD) is the second most common neurodegenerative disorder, with genetic factors accounting for about 15% of cases. There is a significant challenge in tracking disease progression and treatment response, crucial for developing new therapies. Traditional methods like imaging, clinical monitoring, and biomarker analysis have not conclusively tracked disease progression or treatment response in PD. Our previous research indicated that PD patients with increased dopamine transporter (DAT) and tyrosine hydroxylase (TH) in peripheral blood mononuclear cells (PBMCs) might show disease progression and respond to levodopa treatment. Objective: This study evaluates whether DAT- and TH-expressing PBMCs can monitor motor progression in a PD patient with a heterozygous TH mutation. Methods: We conducted a longitudinal follow-up of a 46-year-old female PD patient with a TH mutation, assessing her clinical features over 18 months through DaT scans and PBMC immunophenotyping. This was compared with idiopathic PD patients (130 subjects) and healthy controls (80 age/sex-matched individuals). Results: We found an increase in DAT+ immune cells concurrent with worsening motor scores (UPDRS-III). Following levodopa therapy, unlike idiopathic PD patients, TH+ immune cell levels in this patient remained high even as her motor scores improved. Conclusions: Longitudinal immunophenotyping in this PD patient suggests DAT+ and TH+ PBMCs as potential biomarkers for tracking PD progression and treatment efficacy, supporting further exploration of this approach in PD research.